Glass Corrosion in the Presence of Iron-Bearing Materials and Potential Corrosion Suppressors. Issue 1744 (2015) - Reiser, Joelle; Neill, Lindsey; Weaver, Jamie; Parruzot, Benjamin; Musa, Christopher; Neeway, James; Ryan, Joseph; Qafoku, Nikolla; Gin, Stéphane; Wall, Nathalie A.
ABSTRACT: A complete understanding of radioactive waste glass interactions with near-field materials is essential for appropriate nuclear waste repository performance assessment. In many geologic repository designs, Fe is present both in the natural environment and in the containers that will hold the waste glasses. In this paper we discuss investigations of the alteration of International Simple Glass (ISG) in the presence of Fe 0 foil and hematite (Fe2 O3 ). Based on solid analysis, ISG alteration is more pronounced in the presence of Fe 0 than with hematite. Additionally, typical glass corrosion is observed for distances of 5 mm between Fe materials and ISG, but incorporation of Fe in the alteration layer is only observed for systems exhibiting full contact between Fe 0 material and ISG. Solution analysis results indicate that diatomaceous earth minimizes corrosion to a larger extent than fumed silica does when present with iron and ISG.